Trade Union Membership and Dismissals - Laszlo Goerke; Markus Pannenberg (Center for Economic Studies and ifo Institute (CESifo), 2010)
In Germany, there is no trade union membership wage premium, while the membership fee amounts to 1% of the gross wage. Therefore, prima facie, there are strong incentives to free-ride on the benefits of trade unionism. We establish empirical evidence for a private gain from trade union membership which has hitherto not been documented: in West Germany, union members are less likely to lose their jobs than non-members. In particular, using data from the German Socio-Economic Panel we can show that roughly 50% of the observed raw differential in individual dismissal rates can be explained by the estimated average partial effect of union membership.
Keywords: C23; H41; J51; J63; 330; dismissal; free-riding; trade union membership; survey data; Gewerkschaftlicher Organisationsgrad; Mitgliedschaft; Trittbrettfahrerverhalten; Arbeitsplatzsicherung; Kündigung; Schätzung; Deutschland